Strength and Thermal Properties of Hollow Foamed Concrete Blocks considering Various Parameters - Sulaiman, Abubaker Mohammed; Hilal, Ameer A.; Al-Azzawi, Zaid (Engineering, Technology & Applied Science Research, 2024)
Hot weather is one of the main problems the residential building construction field faces, especially in the southern hemisphere. Therefore, there is an increasing need to produce materials capable of reducing the high temperature impact. These materials should be characterized by thermal insulation properties without, though, their mechanical properties and load resistance being affected. In this research, cuboid and hexagonal hollow concrete blocks were produced from lightweight foam concrete with different hole shapes and a hole ratio of 30%. An analytical study was conducted for 8 models using the ANSYS v16 program, while the compression behavior and thermal performance of the selected models were studied. Ordinary Portland Cement (OPC), water, sand, and foaming agents were deployed in the production of foamed concrete. In addition to the use of admixtures, materials, such as Superplasticizer (SP), Class F Fly Ash (FA), and Silica Fume (SF), were also utilized. Moreover, the effect of the hole’s shape and the method of bonding were studied. The compressive strength of the concrete blocks, bond shear strength, thermal conductivity, and thermal resistance were tested. It was found that the cuboid shape of the hole block H7 was the most acceptable compared to the other shapes, with a compressive strength of 3.75 MPa, thermal conductivity of 0.149 W/m.k, and a bond shear strength of 0.157 MPa. At the same time, it was found that using bonding adhesive material gave the best results, with the cuboid blocks being compared to using mortar and mechanical bonding.